The Refugees’ Right to the Center of the City and Spatial Justice: Gentrification vs Commoning Practices in Tarlabaşı-Istanbul - Tsavdaroglou, Charalampos (2020)
During the recent refugee crisis and following the common statement-agreement between the European Union and Turkey (18 March 2016), more than half a million refugees have been trapped in Istanbul. Although the vast majority is living in remote areas in the perimeter of the city, there is a remarkable exception in the central neighborhood of Tarlabaşı. Over the decades, this area has become a shelter for newcomers from eastern Turkey and, recently, for thousands of refugees from the Middle East and Africa. In this neighborhood, refugees with the support of local and international solidarity groups establish communal houses, social centers, and collective kitchens, creating an example of commoning practices, mutual help, and transnational togetherness in the urban core. At the same time, over the past few years, Tarlabaşı has been the target of gentrification policies that aim to dislocate poor residents and refugees and to transform the area into a highincome residential area and a tourist destination. Thus, ongoing urban conflict is taking place for the right to the center of the city. This article follows the Lefebvrian concept of ‘the right to the city’ and Soja’s and Harvey’s notion of ‘spatial justice,’ taking also into account the discussion on the spatialities of ‘urban commons’ and ‘enclosures.’ It combines spatial analysis, participatory observation, and ethnographic research, and its main findings concern the refugees’ daily efforts against social segregation and exclusion shaped by commoning practices for spatial justice, visibility, and the right to the center of the city.